Awareness and Practice of Junk Foods among Adolescents in Secondary Level Students - Paudel, Radha; Shrestha, Sarita (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Junk food consumption among adolescents has become a serious issue that may lead to harmful effects on health. Dietary patterns of people are shifting from homemade foods to junk foods. Therefore, this study was undertaken to assess the awareness and practice of junk foods among adolescents. Methods: A descriptive cross-sectional study was conducted among adolescents of secondary level students. A simple random sampling technique was used to select the sample and the sample size was 237. Data collection was done from April 15, 2019 to May 14, 2019. A set of semi-structured self-administered questionnaire was used for data collection. Descriptive and inferential statistics were used to analyse and interpret the findings. Results: The findings showed that more than three-fifth (67.9%) of adolescents had a moderate level of awareness about junk foods. Half (49.4%) of them consumed junk foods highly. All (100%) adolescents have consumed junk foods regularly whereas two-fifth (42.2%) replaced meals once a week with junk foods. Four-fifth (82.3%) of adolescents did not bring tiffin from home. There was no significant association between the awareness and practice of junk foods (p < 0.05). Conclusions: This study concludes that most of the adolescents possessed a moderate level of awareness of junk foods. Majority of them did not bring tiffin from their home. Around half of them consumed junk foods in their daily life. Majority of them were aware of junk foods, although they still consumed junk foods.